Therapeutic Potential of Astrocyte Purinergic Signalling in Epilepsy and Multiple Sclerosis - Nobili, Paola; Shen, Weida; Milicevic, Katarina; Bogdanovic Pristov, Jelena; Audinat, Etienne; Nikolic, Ljiljana (Frontiers in Pharmacology, 2022)
Epilepsy and multiple sclerosis (MS), two of the most common neurological diseases, are characterized by the establishment of inflammatory environment in the central nervous system that drives disease progression and impacts on neurodegeneration. Current therapeutic approaches in the treatments of epilepsy and MS are targeting neuronal activity and immune cell response, respectively. However, the emergence and development of therapeutic drug resistance and the lack of fully efficient responses to the available treatments obviously show the urgent need to search for the novel therapeutic candidates that will not exclusively target neurons or immune cells. Accumulating knowledge on epilepsy and MS in humans and analysis of relevant animal models, reveal that astrocytes are promising therapeutic candidates to target as they participate in the modulation of the neuroinflammatory response in both diseases from the initial stages and may play an important role in their development. Indeed, astrocytes respond to reactive immune cells and contribute to the neuronal hyperactivity in the inflamed brain. Mechanistically, these astrocytic cell to cell interactions are fundamentally mediated by purinergic signalling and involve metabotropic P2Y1 receptors in case of astrocyte interaction with neurons, while ionotropic P2X7 receptors are mainly involved in astrocyte interaction with autoreactive immune cells. Herein, we review the potential of targeting astrocytic purinergic signalling mediated by P2Y1 and P2X7 receptors to develop novel approaches for treatments of epilepsy and MS at very early stages.